Endoscopic Lumbar Discectomy Using Side-Viewing Conical Working Tube: An Institutional Experience - Kaif, Mohammad; Yadav, Kuldeep; Khan, Khursheed Alam; Kumar, Rakesh; Singh, Deepak Kumar; Ahmad, Faran (Indian Journal of Neurosurgery, 2022)
Objective The paradigm of surgical therapy for spinal disease especially for lumbar disc herniation (LDH) has gradually shifted from the traditional open surgeries to minimal invasive spinal surgeries. Endoscopic discectomy has been performed widely using various devices and techniques. In this study we present our experience of endoscopic discectomy using a unique device with separate side-viewing channel.Methods Twenty-six patients with LDH treated between March 2015 and April 2018 using the unique conical working tube with separate side-viewing endoscopic channel have been retrospectively analyzed. Their preoperative and postoperative Oswestry Disability Index (ODI) and Macnab scores were used to evaluate the outcome with a mean follow-up of 37.04 months.Results There were 18 males and 8 females with age ranging from 19 to 72 years (mean, 38.4 years). The follow-up ranged from 25 to 60 months with mean of 37.04 months. The mean preoperative ODI score was 72.4, which decreased to a mean of 7.6 and the outcome evaluated by Macnab criteria was 65.3% excellent, 19.2% good, 11.5% fair, and 3.8% poor. One patient underwent second surgery. None of the patients had to change their occupation postoperatively. Complications that occurred were dural tear in one patient and transient foot paresis in one, which improved spontaneously.Conclusion Endoscopic discectomy using conical working tube is a safe and effective technique for lumbar disc prolapse. The long-term results are comparable to the conventional techniques.
Keywords: lumbar disc herniation; endoscopic discectomy; side-viewing channel